Studying professional and recreational female footballers: A bibliometric exercise - Kirkendall, D. T.; Krustrup, P. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Objectives Research directed at soccer has seen dramatic growth in the last decade. While published research on soccer has shown exponential growth, the proportion of articles addressing females is lagging behind research addressing males. The purpose of this paper is to explore how the literature on soccer, female soccer, and professional female soccer has changed over time.